Ciclagem de nutrientes em mangueira - Almeida, Cinara Xavier de; Pita Junior, Jose Luiz [UNESP]; Rozane, Danilo Eduardo [UNESP]; Souza, Henrique Antunes de; Hernandes, Amanda; Natale, William [UNESP]; Ferraudo, Antonio Sergio [UNESP] (Univ Estadual Londrina, 2014)
Estimates of nutrient amounts both shedding and demanding replacement in the maintenance of productivity of fruit trees require studies on element dynamics within the many ecosystem components generally made up of nutrient cycling. Thus, it was the objective of this study to evaluate the nutrient biochemical cycling in a mango tree (Mangifera indica L.) orchard, Palmer variety. Macronutrients [nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S)] had their contents evaluated in leaves at different stages: new, mature, senescent, and litter. First exploratory analysis was performed for main components which preserve the multivariate structure shown by the data. It was possible to observe the association of new leaves with N, P, K, Mg, and S; senescent leaves and the leaves from the litter were associated to Ca, while mature leaves, to K. As a complement, taking the independent variables into consideration, Tukey test (p=0.01) showed that the averages of N, P, and Ca differ between the new and the mature leaves; average of Mg in new leaves differs from the others, and S does not differ along the stages. Also observed was the re-translocation of 41%, 63% and 57% of N, P, and K, respectively, when comparison was made among the contents of the elements in mature leaves as well as in litter, which indicates that the biochemical cycling is important for the mango tree cultivation.
Nutrient cycling in mango trees
Keywords: Mangifera indica L.; biochemical bycling; main components